Perbedaan Hitung Jumlah Trombosit Menggunakan Darah Vena dan Darah Kapiler - Hieronymus Rayi Prasetya; Maria Irena Dentri; Sistiyono Sistiyono (LPPM STIKES Guna Bangsa, 2016)
Background: Platelets play a role in hemostasis which is the body's mechanisms to prevent and stop the bleeding. Platelets participate in the effort to close the wound, so that the body does not experience a loss of blood and protected from foreign cells. Examination of the platelet count is very important in the diagnosis of diseases, one of which is the diagnosis of dengue hemorrhagic fever (DHF). Examination of blood counts, especially platelets in clinical laboratories causes blood samples in use are not always the venous blood but could use capillary blood. Capillary blood samples are used primarily in pediatric patients, because the venous blood sampling is difficult, patient loads, and also shorten the time when taking blood. The purpose of this study was to determine whether there is a difference in counting the number of platelets using samples of blood veins and capillaries. Methods: Quantitative research with observational approach using a cross sectional study design in the 30 samples of student D3 Health Analyst STIKes To Nation Yogyakarta. Statistical methods in use are independent T test. Results: The research subjects were 30 samples of student D3 Health Analyst STIKes To Nation Yogyakarta. The results of the examination of venous blood platelet count and blood capillaries have different average values ​​are 247 530 cells / ml of blood, for blood platelets veins and 184 270 cells / ml of blood for capillary blood platelets. Spearman correlation analysis Obtained results of the examination of venous blood platelet count and blood capillaries normal distribution (p> 0.05). 0.129 venous blood platelet counts, while the number of blood platelets kapilernya 0.089. Conclusion: There is a significant difference from the results of counting the number of blood platelets using veins and capillaries, where the use of capillary blood samples showed that lower platelet counts.